2003
DOI: 10.1002/macp.200390005
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Nature of Active Sites on TiCl4/MgCl2 Ziegler–Natta Catalyst in the Presence of an Internal Electron Donor

Abstract: Based on our previous study on the donor‐free TiCl4/MgCl2 catalyst, the stereospecific nature of active sites on this catalyst after the addition of an internal donor, ethylbenzoate (EB), was investigated by stopped‐flow propylene polymerization combined with temperature rising elution fractionation (TREF) and gel permeation chromatography (GPC) methods. The addition of donor EB was observed to significantly restrain the formation of aspecific sites (AS sites), to drastically promote formation of sites with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 66 publications
3
78
0
1
Order By: Relevance
“…Liu et al 15 proposed four types of active sites based on TREF analysis of produce. Kissin et al 16 considered that polymers produced with any heterogeneous Tibased catalyst consist of at least four or five Folry components.…”
Section: Active Site Modelmentioning
confidence: 99%
“…Liu et al 15 proposed four types of active sites based on TREF analysis of produce. Kissin et al 16 considered that polymers produced with any heterogeneous Tibased catalyst consist of at least four or five Folry components.…”
Section: Active Site Modelmentioning
confidence: 99%
“…[1] In the three-sites and its modified models, [2,3] a series of active Ti species whose bulkiness is increased by Cl, donors, or alkylaluminum compounds coordinating at one or two neighboring metal ions to a Ti 3þ site were proposed as isospecific centers.…”
Section: Introductionmentioning
confidence: 99%
“…Internal donor is added during the catalyst synthesis, while external donor is added during polymerization reaction. The main functions of external donor are to replace the lost internal donor, which is removed from the alkylation and/or complexation reaction with cocatalyst and protect the stereoregularity of active sites in propylene polymerization [11,12]. In part of ethylene polymerization, Zhang et al observed that electron donor has a large effect not only on the isospecificity, but also on the catalyst activity, molecular weight and molecular weight distribution in ethylene homopolymerization [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the addition of internal donor can improve the activity. As described previously, the various kinds of electron donors were used in olefin polymerization such as monoester, diester, alkoxysilane, diether and etc [11,14]. Recently, phthalate based type or diester and alkoxysilane are typically used as internal and external donor, respectively [15].…”
Section: Introductionmentioning
confidence: 99%